2009
DOI: 10.1177/1545109709337745
|View full text |Cite
|
Sign up to set email alerts
|

Obstacles and Proposed Solutions to Effective Antiretroviral Therapy in Resource-Limited Settings

Abstract: More than 3 million people were receiving antiretroviral therapy (ART) at the end of 2007, but this number represents only 31% of people clinically eligible for ART in resource-limited settings. The primary objective of this study is to summarize the key obstacles that impede the goal of universal access prevention, care, and treatment. We performed a systematic literature search to review studies that reported barriers to diagnosis and access to treatment of HIV/AIDS in resource-limited countries. Persons liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 28 publications
1
13
0
1
Order By: Relevance
“…The nearly half day waiting time caused them to forego income from not working, particularly among those patients who had fixed-hour jobs and were required to be absent from work to receive treatment. This problem is similar to the findings of the study by Bartlett et al44 which show that some patients had to be absent from work in order to receive treatment due to inappropriate service times. In terms of the date and time of ART service, only 14.7% of all respondents deemed the days and hours to be inappropriate due to the fact that the service for ART was normally available during the same periods of other general health care services, so HIV/AIDS patients more or less were forced to reveal their identities; this result reflects the patients’ fears of social stigma.…”
Section: Discussionsupporting
confidence: 87%
“…The nearly half day waiting time caused them to forego income from not working, particularly among those patients who had fixed-hour jobs and were required to be absent from work to receive treatment. This problem is similar to the findings of the study by Bartlett et al44 which show that some patients had to be absent from work in order to receive treatment due to inappropriate service times. In terms of the date and time of ART service, only 14.7% of all respondents deemed the days and hours to be inappropriate due to the fact that the service for ART was normally available during the same periods of other general health care services, so HIV/AIDS patients more or less were forced to reveal their identities; this result reflects the patients’ fears of social stigma.…”
Section: Discussionsupporting
confidence: 87%
“…HIV positive individuals who did not disclose their HIV status to their spouses/partners were more likely to present late to HIV/AIDS care compared with those who disclosed their HIV status, studies done elsewhere [9,12] supports this finding. This could be explained that the desire to hide one's HIV-positive status from a spouse may inhibit HIV care-seeking.…”
Section: Discussionmentioning
confidence: 77%
“…A prospective study from New York City found significantly higher rates of TB, AIDS, and death for substance users on welfare than for the general population of New York City (risk ratios of 15, 10, and 5, respectively) (100). In addition, HIV-infected persons living in resource-constrained settings face socioeconomic and behavioral barriers to HIV testing and access to antiretroviral treatment (16). Without adequate urban planning and investment in equitable urban health care systems, including integrated TB and HIV programs, the rise in slum areas and urban poverty will continue to propel the transmission of HIV-associated TB and its associated morbidity and mortality.…”
Section: Urban Population Growth May Escalate the Hiv And Tb Syndemicmentioning
confidence: 99%